Effects of DNA methylation on cardiometabolic risk factors: a systematic review and meta-analysis - Zahra Barouti; Motahar Heidari-Beni; Anahita Shabanian-Boroujeni; Morteza Mohammadzadeh; Vida Pahlevani; Parnian Poursafa; Fatemeh Mohebpour; Roya Kelishadi (BMC, 2022)
Abstract Background Epigenetic changes, especially DNA methylation have a main role in regulating cardiometabolic disorders and their risk factors. This study provides a review of the current evidence on the association between methylation of some genes (LINE1, ABCG1, SREBF1, PHOSPHO1, ADRB3, and LEP) and cardiometabolic risk factors. Methods A systematic literature search was conducted in electronic databases including Web of Science, PubMed, EMBASE, Google Scholar and Scopus up to end of 2020. All observational human studies (cross-sectional, case-control, and cohort) were included. Studies that assessed the effect of DNA methylation on cardiometabolic risk factors were selected. Results Among 1398 articles, eight studies and twenty-one studies were included in the meta-analysis and the systematic review, respectively. Our study showed ABCG1 and LINE1 methylation were positively associated with blood pressure (Fisher's zr = 0.07 (0.06, 0.09), 95% CI: 0.05 to 0.08). Methylation in LINE1, ABCG1, SREBF1, PHOSPHO1 and ADRB3 had no significant association with HDL levels (Fisher's zr = − 0.05 (− 0.13, 0.03), 95% CI:-0.12 to 0.02). Positive association was existed between LINE1, ABCG1 and LEP methylation and LDL levels (Fisher's zr = 0.13 (0.04, 0.23), 95% CI: 0.03 to 0.23). Moreover, positive association was found between HbA1C and ABCG1 methylation (Fisher's zr = 0.11 (0.09, 0.13), 95% CI: 0.09 to 0.12). DNA methylation of LINE1, ABCG1 and SREBF1 genes had no significant association with glucose levels (Fisher's zr = 0.01 (− 0.12, 0.14), 95% CI:-0.12 to 0.14). Conclusion This meta-analysis showed that DNA methylation was associated with some cardiometabolic risk factors including LDL-C, HbA1C, and blood pressure. Registration Registration ID of the protocol on PROSPERO is CRD42020207677 .